LITERATURE REVIEW FAKTOR-FAKTOR YANG BERKETERKAITAN DENGAN KEJADIAN SCABIES PADA ANAK - PUTRI SEPTIANI; Miftah Apriani; Dewi Ciselia (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2026)
Scabies is a skin disease commonly found in tropical and subtropical climates and is contagious. Another word commonly used by Indonesians to describe scabies is